Finite Element Modeling of Stamp Forming Process on Thermoplastic-Based Fiber Metal Laminates at Elevated Temperatures - Sivakumar, Dhar Malingam (Scientific Research Publishing, 2015)
This paper investigated stamp forming performance of two aluminum-based Fiber-metal laminates (FMLs) with different fiber-reinforced composites using finite element analysis. Given the inherent thermal-dependent properties of fiber-reinforced polypropylene, the effect of elevated temperature on its forming behavior is worthy of concern. Furthermore, the elevation in temperature also influences the bonding within the constituent lamina. Both factors were integrated in the modelling. By investigating the through-thickness strain evolution throughout the stamping process, the forming mode of each layer, as well as their interactions, were better understood. Results suggested that the flow of matrix and the rotation at the intersections of fiber strands can be promoted at elevated temperature, which transforms the forming performance of FMLs close to that of monolithic aluminum. These results propose means to improve the forming performance of FMLs.